Gender diversity in the boardroom. Volume 1, - Seierstad, Cathrine; Gabaldon Quinones, Patricia; Mensi-Klarbach, Heike (Palgrave Macmillan, 2017)
This edited collection provides a structured and in-depth analysis of the current use of quota strategies for resolving the pressing issue of gender inequality, and the lack of female representation on corporate boards. Filling the gap in existing literature on this topic, the two volumes of Gender Diversity in the Boardroom offers systematic overviews of current debates surrounding the optimisation of gender diversity, and the suggested pathways for progress. Focusing on sixteen European countries, the skilled contributors explore the current situation in relation to women on boards debates and approaches taken. They include detailed reflections from critical stakeholders, such as politicians, practitioners and policy-makers. Volume 1 focuses on eight European countries having adopted quotas and is a promising and highly valuable resource for academics, practitioners, policy makers and anyone interested in gender diversity because it examines and critiques the current corporate governance system and national strategies for increasing the share of women not only on boards, but within companies beyond the boardroom.